A culturally adapted survivorship programme for Asian early stage breast cancer patients in Singapore: A randomized, controlled trial. Issue 10 (25th January 2017) - Chan, Alexandre; Gan, Yan Xiang; Oh, Suan Kai; Ng, Terence; Shwe, Maung; Chan, Raymond; Ng, Raymond; Goh, Brandon; Tan, Yee Pin; Fan, Gilbert
Abstract: Background: As cancer mortality rates improve in Singapore, there is an increasing need to improve the transition to posttreatment survivorship care. This study aimed to evaluate the effectiveness of a psychoeducation group (PEG) intervention program compared with usual care to reduce distress for physical symptom and psychological aspects in Asian breast cancer survivors who have completed adjuvant chemotherapy. Methods: This was a randomized, controlled trial comprising 72 Asian early stage breast cancer survivors who were randomized into the PEG (n = 34) or the control (n = 38) arm. The participants in the PEG arm underwent a weekly multidisciplinary PEG program delivered in a group format over 3 weeks coupled with cultural adaptation. Both arms were assessed at baseline and 2 months after intervention using the Rotterdam Symptom Checklist, Beck Anxiety Inventory, and EORTC QLQ‐C30. A satisfaction questionnaire was also conducted among those survivors who have participated in the PEG program. Effective sizes were calculated using Cohen d . Results: The mean age ± SD of all participants was 53.0 ± 8.9 years, with the majority being Chinese (84.7%) and Malay (6.9%), and clinical characteristics were well balanced in both arms. Compared to the control arm, the PEG arm showed a significantly greater reduction in physical symptom distress ( d = 0.76, P = .01) and fatigue ( d = 0.49, P = .04). The 82.4% of the participants in the intervention group responded to the satisfaction questionnaire, and the majority (92.9%) agreed that the overall duration of the PEG intervention program was appropriate. Conclusions: A culturally adapted PEG program was effective in reducing physical symptom distress in Asian breast cancer survivors. (ClinicalTrials.gov : NCT02600299)